Transcriptional adaptation of staphylococci during colonization of the authentic human environment: An overview of transcriptomic changes and their relationship to physiological conditions - Burian, Marc; Wolz, Christiane; Yazdi, Amir S. (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococci are commensals of human skin and mucous membranes, but some species can also cause serious infections. Host niches during both colonization and infection differ greatly and are characterized by specific environmental conditions (pH, temperature, oxygen, nutrient availability, and microbiota) that can affect gene expression and virulence of microbes. To successfully occupy extremely different habitats at different anatomical sites, Staphylococci are equipped with a variety of regulatory elements that allow specific adaptation to the changing environments. Not surprisingly, gene expression in vivo can be significantly different from the expression pattern observed in vitro. Niche specific stimuli that influence the bacterial ability to either cause infection or maintain colonization are only partially understood. Here, we describe habitat specific conditions and discuss the available literature analyzing staphylococcal gene expression during colonization of the nose and skin.